Spatial Ability and Digital Literacy Profiles: Preceding Survey on the Need of Augmented Reality Media in Chemistry Instruction - Yuyun Yulianti; Indarini Dwi Pursitasari; Irvan Permana (Indonesian Journal Of Educational Research and Review, 2022)
Students are demanded to be equipped with a sufficient level of multiliteracy to perform 21st Century Skills which include spatial ability and digital literacy. Spatial ability is needed to solve problems in chemistry lessons. In addition to spatial ability, digital literacy is also required to face industry 4.0. This research is aimed to analyze both spatial ability and digital literacy skills along with the media that could help develop the two skills. The research method used is descriptive qualitative method uses a survey to collect the data. This study was carried out on 922 senior high school students from four schools and 35 teachers. Purdue Spatial Visualization Test (PSVT), Likert-scale questionnaire, and closed-ended questionnaire were used as the instruments. The results indicate that 98% of the students are of low category in spatial ability while those showing mid and high category each only consists of 1%. However, in terms of the digital literacy index, the students generally score mediocre. The results from the media need a questionnaire on chemistry instruction to indicate that Augmented Reality-based media is needed both by teachers and students. Therefore, to help improve the students’ spatial ability and digital literacy, a teaching media that visualizes both abstract and concrete objects is needed.